Prevalence of Workplace‐Related Musculoskeletal Disorders Among Nurses and Midwives in a Tertiary Healthcare Facility: A Descriptive Cross‐Sectional Survey - Iddrisu Sisala Mohammed; Mohammed Hardi Abdulai; Mudasir Mohammed Ibrahim; Hannah Buasilenu; Issahaka Abdulai Baako; Brenda Abena Nyarko; Abubakari Wuni; Camillus Buunaaisie (Wiley, 2024)
ABSTRACT Aim To assess the prevalence of workplace‐related musculoskeletal disorders (WMSDs) among Nurses and Midwives in a Tertiary Healthcare Facility in Northern Ghana. Methods The study utilised a descriptive cross‐sectional study design using the STROBES guidelines. Standardised Nordic musculoskeletal questionnaire was used to gather data from 309 nurses and midwives. The selection of respondents was done using a simple random sampling method. The data were analysed using SPSS version 27.0. Results From the 259 included respondents, 195 (75.3%) experienced WMSDs in the last 12 months. 138 (70.7%) highlighted their low back (lumbar/sacral) as the affected region and 119 (61.0%) indicated experiencing WMSDs during the first 5 years of clinical practice. Key job‐related risk factors contributing to WMSDs development included working in the same positions (such as standing, bending over, sitting, kneeling) for long periods (176 [68.0%]), treating an excessive number of patients in 1 day (142 [54.8%]), continuing to work while injured or hurt (139 [53.7%]), bending or twisting the back in an awkward way (140 [54.1%]) and not enough rest breaks or pauses during the workday (130 [50.2%]). Regarding coping strategies, the most frequently employed method was getting someone else to help handle a heavy patient (83 [42.5%]). The multivariate regression analysis revealed that respondents with fewer than 5 years of experience were markedly more susceptible to reporting WMSDs compared to those with over 10 years of experience (AOR = 3.73, 95% CI [1.03, 13.42], p = 0.043). Conclusion The overall prevalence of WMSDs among nurses and midwives was high. This study also revealed that the most commonly affected body region was their low back. Working in the same position for long periods was identified as a major occupational risk factor contributing to these disorders. Despite this risk, a significant number of nurses and midwives consistently sought assistance when handling heavy patients. The current study suggests that hospitals should provide comprehensive ergonomic training to healthcare professionals, emphasising proper body mechanics, posture and techniques for patient moving and handling. Patient or Public Contribution Patients or public were not involved in setting the research objectives, the design and preparation of the manuscript. Nurses and midwives working the tertiary hospital answered the research questionnaires.